2021
DOI: 10.1101/2021.11.05.21265849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humoral immune response to Covid-19 vaccination in diabetes: age-dependent but independent of type of diabetes and glycaemic control – the prospective COVAC-DM cohort study

Abstract: AimsImmune response to COVID-19 vaccination and a potential impact of glycaemia on antibody levels in people with diabetes remains unclear. We investigated the seroconversion following first and second COVID-19 vaccination in people with type 1 and type 2 diabetes in relation to glycaemic control prior to vaccination and analysed the response in comparison to individuals without diabetes.Materials and MethodsThis prospective, multicenter cohort study analysed people with type 1 and type 2 diabetes, well (HbA1c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
(22 reference statements)
5
10
0
Order By: Relevance
“…This finding is in line with our previous observation of the humoral immune response following the second COVID-19 vaccination, which was similar in people with and without diabetes, 6 but in contrast to another study suggesting a reduced immune response in people with diabetes, 8 which used the GenScript SARS-CoV-2 surrogate virus neutralization test in contrast to the Roche Elecsys anti-SARS CoV-2 S assay targeting the RBD in our study, which might explain the difference in the finding.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is in line with our previous observation of the humoral immune response following the second COVID-19 vaccination, which was similar in people with and without diabetes, 6 but in contrast to another study suggesting a reduced immune response in people with diabetes, 8 which used the GenScript SARS-CoV-2 surrogate virus neutralization test in contrast to the Roche Elecsys anti-SARS CoV-2 S assay targeting the RBD in our study, which might explain the difference in the finding.…”
Section: Discussionsupporting
confidence: 93%
“…Our research group previously showed that humoral immune response 2‐3 weeks after the second COVID‐19 vaccination is similar in people with type 1 diabetes, type 2 diabetes and healthy controls, 6 irrespective of glycaemic control. Recent data suggest that anti‐severe acute respiratory syndrome coronavirus 2 spike protein (SARS‐CoV‐2S) antibody levels decline more rapidly in people with diabetes; however, it remains unclear if there is a difference between people with type 1 diabetes and type 2 diabetes and if glycaemic control impacts the decline 7 …”
Section: Contextmentioning
confidence: 85%
See 2 more Smart Citations
“…A previous report included 81 people with type 2 diabetes and found lower IgG and neutralising titers in this group [28]. In contrast, another report included a mixture of 150 people with type 1 and type 2 diabetes found no decline in IgG post-vaccination in diabetics [29]. However, vaccine efficacy appears to be maintained despite lower antibody responses.…”
Section: Discussionmentioning
confidence: 90%